2020
DOI: 10.2478/fhort-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the fruiting period and growing seasons on market quality in goji berry (Lycium barbarum L.)

Abstract: Progression of the vegetation period and change of year are associated with variations in general climatic parameters, such as temperature, atmospheric pressure, humidity, radiation, precipitation, wind speed and others. Only limited knowledge is available about the effects of these parameters on the characteristics of quality of fruits especially those with successive ripening such as goji berry. In our study, fruits of goji berry were characterised based on physico-chemical properties within four different h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
1
18
1
Order By: Relevance
“…Lycium chinense fruits contain higher titratable acidity (1.6-1.9%) than L. barbarum fruits (0.8-1.4%). But according to the data of Polat et al (2020), the titratable acidity content of L. barbarum fruits was significantly lower (0.48-0.62%) than shown in from the previous study. The titratable acidity of the fruit is also related to the harvest period and the colour of the goji fruit.…”
Section: Discussioncontrasting
confidence: 67%
“…Lycium chinense fruits contain higher titratable acidity (1.6-1.9%) than L. barbarum fruits (0.8-1.4%). But according to the data of Polat et al (2020), the titratable acidity content of L. barbarum fruits was significantly lower (0.48-0.62%) than shown in from the previous study. The titratable acidity of the fruit is also related to the harvest period and the colour of the goji fruit.…”
Section: Discussioncontrasting
confidence: 67%
“…The highest value in terms of soluble solid content was found in 'Regina', while Starks Gold (13.17%) with white fruit skin and flesh colour and Early Burlat (14.91%) which is an early cultivar were found to have the lowest value in terms of this feature. In studies conducted with of different species, it has been reported that phytochemical accumulation is lower in early cultivars with a shorter period from full bloom to harvest and in the cultivars with lighter fruit flesh and skin color (Eskimez et al, 2020;Polat et al, 2020a). Conversely, as duration of remaining on the branch of the fruit increases, organic acids, which have a lower degradation coefficient in respiration than other compounds, are primarily used as breakdown products in metabolic events.…”
Section: Resultsmentioning
confidence: 99%
“…It is determined that obtained results are largely in line with previous studies. Although the differences are thought to be mainly caused by the variation of the examined varieties, differences in climate and soil characteristics, the geographical situation of the area where the cultivation is made, the type and time of harvest, the storage or processing of the crop, the method or periodic differences of the applied cultural processes cause significant differences on the final form of the phytochemical composition (Tiwari and Cummins, 2013;Polat et al, 2020a). Changes in phytochemical properties in parallel with the change of ecological factors and growing conditions were reported (Mertoğlu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the most important commercially grown horticultural crops in temperate zones of the world [7,8]. Apples are rich in antioxidants such as α-tocopherol that have antiageing and anticancer properties [8][9][10]. Furthermore, apples have a unique flavour that makes them acceptable by many consumers worldwide [11].…”
Section: Introductionmentioning
confidence: 99%